1999
DOI: 10.1159/000057140
|View full text |Cite
|
Sign up to set email alerts
|

Regulationstherapie: Behandlung mit unspezifischen Reizen in der Dermatologie aus traditioneller und moderner Sicht

Abstract: Stimulation or regulation therapies are old therapeutic procedures based on models reaching back to traditional medical faculties in ancient times and in the Middle Ages. Among this heterogeneous group are acupuncture, purgative procedures (especially the Aschner methods), autohemotherapy, fasting therapy, homeopathy, microbiological and physical therapies. The basic principle underlying all of these procedures is that stimulants applied in proper doses to the organism elicit counterregulation. The counterregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…ABT belongs to the stimulation or regulation therapies. These are based on the principle that a stimulus applied to the body elicits a counter‐regulation, which in turn stimulates a beneficial response 11 . It has been suggested that effects on immune parameters such as interleukin‐10 or parameters that are thought to invigorate the immune system are involved 11–13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABT belongs to the stimulation or regulation therapies. These are based on the principle that a stimulus applied to the body elicits a counter‐regulation, which in turn stimulates a beneficial response 11 . It has been suggested that effects on immune parameters such as interleukin‐10 or parameters that are thought to invigorate the immune system are involved 11–13 .…”
Section: Discussionmentioning
confidence: 99%
“…A treatment option that is used in some European countries 9,10 is autologous blood therapy (ABT). This treatment, which involves the taking of relatively small amounts of venous blood followed by intramuscular reinjection, has been reported to have beneficial effects for patients with AD 11 . Evidence from animal experiments suggests that ABT has modulating effects on immune function 12,13 .…”
mentioning
confidence: 99%
“…ABT involves the repeated administration of small amounts of autologous blood (1-10 ml) by intramuscular injection immediately after sampling of venous blood [17]. ABT has been used as complementary and alternative medicine for AD and chronic urticaria (CU) by physicians in many countries, including those in Europe and Japan, since its first report in 1913 [18]. ABT is reportedly the most frequently used complementary and alternative medicine modality for AD by physicians in Germany [19].…”
Section: Discussionmentioning
confidence: 99%
“…Survey of physicians in Germany have shown ABT as the most frequently used complementary alternative medicine for AD 10. ABT has been used for about 100 years in many countries for the treatment of various chronic diseases 11. ABT is a treatment of repeatedly administering small amounts of autologous blood (1-5 mL) by intramuscular injection immediately after the sampling of venous blood from a patient 9.…”
Section: Discussionmentioning
confidence: 99%